2016
DOI: 10.1089/vbz.2015.1863
|View full text |Cite
|
Sign up to set email alerts
|

Zoonotic and Vector-Borne Infections Among Urban Homeless and Marginalized People in the United States and Europe, 1990–2014

Abstract: B. quintana was the most frequently reported vector-borne infection identified in our article. Delousing efforts and active surveillance among HIV-positive individuals, who are at elevated risk of complication from B. quintana infection, are advised to reduce morbidity. Given documented exposure to rodent-borne zoonoses among urban homeless and marginalized people, reducing human contact with rodents remains an important public health priority.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
45
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(55 citation statements)
references
References 76 publications
4
45
1
Order By: Relevance
“…The mice were also trapped outside the NoV epidemic season. As far as we know, no one, us included, has been able to detect HuNoVs in mouse samples (Leibler et al., ; Lõhmus, Janse, van de Goot, & van Rotterdam, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mice were also trapped outside the NoV epidemic season. As far as we know, no one, us included, has been able to detect HuNoVs in mouse samples (Leibler et al., ; Lõhmus, Janse, van de Goot, & van Rotterdam, ).…”
Section: Discussionmentioning
confidence: 99%
“…Wildlife is known to serve as a source of many zoonotic pathogens such as salmonella and rabies (Kruse, Kirkemo, & Handeland, ). Rats and other small rodents are commonly found to spread various human diseases, such as salmonella and plague, but can also carry hepatitis E and hantaviruses (Kosoy, Khlyap, Cosson, & Morand, ; Leibler, Zakhour, Gadhoke, & Gaeta, ; Vaheri, Henttonen, Voutilainen, Mustonen, & Vapalahti, ). Furthermore, wild birds reportedly transmit at least salmonella, mycobacteria, West Nile virus and influenza viruses to humans (Tsiodras, Kelesidis, Kelesidis, Bauchinger, & Falagas, ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the effects of rats on infrastructure and food supply (Doherty, Glen, Nimmo, Ritchie, & Dickman, ), rat infestations also pose health risks to humans (Himsworth, Parsons, Jardine, & Patrick, ; Himsworth, Bidulka et al., ; Ko, Reis, Dourado, Johnson, & Riley, ; Meerburg, Singleton, & Kijlstra, ). Brown rats are known hosts of several human pathogens that cause important zoonotic diseases, including Seoul hantavirus, leptospirosis and bubonic plague (Costa et al., ; Himsworth et al., ; Leibler, Zakhour, Gadhoke, & Gaeta, ). High rat densities increase the likelihood of human–rat contact, posing an acute risk to public health because zoonotic pathogens or ectoparasite vectors can be transmitted during rodent encounters (Frye et al., ; Himsworth, Parsons et al., ; Rogalski, Gowler, Shaw, Hufbauer, & Duffy, ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, a recent review of published epidemiologic studies of zoonotic and vector‐borne infections among urban homeless reported Bartonella spp. as the most frequently identified vector‐borne infection (Leibler et al., ). Other zoonotic pathogens that were commonly detected among the people sampled included Seoul hantavirus, Leptospira interrogans and Rickettsia typhi (Leibler et al., ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation